On New Inequalities via Riemann-Liouville Fractional Integration - Mehmet Zeki Sarikaya; Hasan Ogunmez (Abstract and Applied Analysis)
We extend the Montgomery identities for the Riemann-Liouville fractional integrals. We also use these Montgomery identities to establish some new integral inequalities. Finally, we develop some integral inequalities for the fractional integral using differentiable convex functions.